THE ROLE OF NUTRITION AND HYDRATION TOWARD THE TENNIS BALL PLAYERS' PERFORMANCE - Cerika Rismayanthi (Jorpres (Jurnal Olahraga Prestasi), 2016)
When practicing or matching, the tennis players will have many sweats. There will many sweats again, if they do sport exercise in a hot place. The sweats from the body can achieve a liter per hour. Many of tennis players, who do not know how many liquid that out from the body through the sweat when they play, practice or have a match. For men or women teenage players, they produce around one to two and a half liters sweats a day.   However,  for some professional players, that produce can get more until three and a half liters a day in a competition season.If the body lost more than 2 % water from the total of body weight, it will cause dehydration (lack of the body's liquid) and can disturb their health. To prevent the dehydration, it is better for tennis players to drink before they feel thirsty. Drink water regularly with little electrolyte and carbohydrate are better to prevent the dehydration. It is suggested to drink juice from fresh fruits because of water and electrolyte in it which is needed to change the lost water and liquid from the body along practicing or having a match. Keywords: nutrition, hydration, tennis ball athletes' performance